Factors Influencing Consumer Behavior Towards Ornamental Plants Purchase Decisions (Case Study: Roni Flower in Rumbai District, Pekanbaru City) - Manik, Desi Irawasih; Nizar, Rini; Amalia (JURNAL AGRIBISAINS, 2026)
The growing popularity of ornamental plants has increased business opportunities in this sector, including at Roni Flower in Rumbai District, Pekanbaru City. However, business owners still face challenges in understanding the factors that influence consumers’ purchasing decisions for ornamental plants. A better understanding of consumer behavior is essential to develop more effective and targeted marketing strategies. This study aims to analyze the influence of cultural, social, personal, and psychological factors on consumers’ purchasing decisions for ornamental plants at Roni Flower. The research employed a quantitative approach using a survey method involving consumers who had previously purchased ornamental plants. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that social and personal factors influence consumers’ purchasing decisions, while cultural and psychological factors do not significantly influence purchasing decisions. These findings suggest that consumers’ decisions to purchase ornamental plants are more strongly shaped by social interactions and personal characteristics, such as lifestyle and individual preferences, rather than by cultural values or internal psychological considerations. Based on these findings, ornamental plant businesses are encouraged to strengthen marketing strategies that leverage social influence, such as utilizing social media, collaborating with plant enthusiast communities, and organizing educational activities related to ornamental plant care. In addition, business owners should align their products with consumers’ preferences and lifestyles to enhance product attractiveness and sustain market demand.